117k views
3 votes
Question 1 Post Math

Question 1 Post Math-example-1
User Cheezey
by
5.1k points

1 Answer

4 votes

ANSWER

Yes, k=-3 and y=-3x

Step-by-step explanation

Let's assume y varies directly as x.

Then, we can write the equation:

y=kx

From the table, when x=1, y=3

Substitute these values to obtain;

3=-k

This implies

k=-3

The equation now becomes:

y=-3x

We check for a second point to see if it satisfy the equation.

When x=5,y=-15

-15=-3(5)

-15=-15

Hence the relation represent a direct variation.

User Jeremy Smith
by
6.0k points